BENARKAH ISRAEL MELAKUKAN KEJAHATAN GENOSIDA TERHADAP PALESTINA? : PERSPEKTIF MANTAN JAKSA PENUNTUT UMUM MAHKAMAH PIDANA INTERNASIONAL - Purwono, Prahoro Yudo (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2024)
This research aims to elucidate the inferential meanings in the utterances of Luis Moreno Ocampo, an Argentine lawyer who served as the first Chief Prosecutor of the International Criminal Court (ICC) from 2003 to 2012, overseeing investigations into war crimes, genocide, and crimes against humanity; and the UpFront host during the interview. The implications of this study are to assist readers, particularly viewers and listeners of the UpFront program, in understanding the inferential meanings of the speakers, thereby enabling the broader community to fully comprehend the speakers' intentions and avoid misinterpretations of the discourse presented. The research method employed is qualitative research with a contextual meaning analysis (pragmatic) approach, following the relevance theory by Sperber and Wilson (2012a). The results of the research indicate that The 1st Speaker (and continuely written as SPK 1, refers to Up Front program hostaims to validate claims of Israeli involvement in war crimes and genocide during the UpFront program, by highlighting the pursuit of justice in the Israel-Palestine conflict. SPK 2 (the 2nd speaker, refers to Luis Moreno Ocampo) offers a broader perspective by acknowledging the responsibility shared between Hamas and Israel for the atrocities committed, rather than solely blaming one party. SPK 2 also intends to emphasize the challenges faced by international legal institutions such as the International Criminal Court in holding perpetrators accountable. Inferentially, SPK 2 seeks global cooperation to combat genocide and promote peace, particularly emphasizing the importance of collective action based on solidarity in addressing the ongoing humanitarian crisis.